The Influence of Organizational Justice, Work-Life Balance, and Organizational Culture on Employee Performance Mediated by Employee Engagement at the Financial Services Authority - Sukma Aji Wirawan; Antyo Pracoyo; Batara Maju Simatupang; Bambang Budhijana (Jurnal Inovasi Global, 2026)
This research examines the influence of organizational justice, work-life balance, and organizational culture on employee performance, mediated by employee engagement. This analysis uses organizational justice, work-life balance, and organizational culture as exogenous variables, employee performance as an endogenous variable, and employee engagement as a mediating variable. The sampling technique employs Slovin sampling with a non-probability sampling method. The sample in this study comprised employees who were actively working at the Financial Services Authority (OJK) Head Office, involving 69 participants. The analysis technique used is partial least squares analysis. The results of the study are as follows: (1) organizational justice has a significant effect on employee performance; (2) work-life balance does not have a significant effect on employee performance; (3) organizational culture has a significant effect on employee performance; (4) employee engagement has a significant effect on employee performance; (5) organizational justice has a significant effect on employee engagement; (6) work-life balance has a significant effect on employee engagement; and (7) organizational culture has a significant effect on employee engagement. The managerial implication is that OJK Head Office HR managers are expected to regularly review employee work quality to ensure it aligns with POJK 48/2024 concerning good governance for PVML. This is crucial to ensure employees can work with a focus on excellent public service quality. Leadership also needs to demonstrate appreciation for each employee's performance to ensure they feel valued.